Massive transfusion protocol in obstetrics - La Rosa, Mauricio (2020)
Obstetric hemorrhage is the most common cause of maternal mortality in the world. Our knowledge of hemorrhagic shock pathophysiology and management has significantly improved during the last decades. Blood transfusion has emerged as a strategy with great impact on patients’ survival. Consequently, it is crucial to have a protocol of massive blood transfusion available for cases of massive obstetric hemorrhage.